Cross-sectional study of the association between cataract surgery and age-related macular degeneration in the era of phacoemulsification in the national health and nutrition examination survey 2005–2008 - Jian Zhang; Wei Wang; Stuart Keel; Mingguang He; Zhuoting Zhu; Huan Liao (BMJ Open)
Objective To determine the association between cataract surgery and age-related macular degeneration (AMD) in a representative US sample.Design Population-based, cross-sectional study.Setting The US National Health and Nutrition Examination Survey 2005–2008.Participants A total of 5401 participants aged ≥40 years had information in cataract surgery status and gradable retinal photographs for right eyes.Methods Cataract surgery status was obtained from questionnaire. Non-mydriatic fundus photographs were collected and AMD status was assessed. The associations between AMD and cataract surgery were evaluated in right eyes using logistic regression models.Results Of 338 right eyes with any AMD, 107 right eyes (28.9%) had cataract surgery. After adjusting for multiple variables, there were significant associations between cataract surgery and any AMD (OR 1.36; 95% CI 1.03 to 1.81) or late AMD (OR 2.48; 95% CI 1.01 to 6.09). No significant association was found between cataract surgery and early AMD after adjusting for multiple covariates (OR 1.20; 95% CI 0.91 to 1.59).Conclusion Our results suggest that cataract surgery is associated with the presence of AMD, particularly for late AMD. Longitudinal studies investigating the risk and progression of AMD after cataract surgery are needed in the era of phacoemulsification.